A novel grid-connected solar PV-thermal/wind integrated system for simultaneous electricity and heat generation in single family buildings. (20th October 2021) - Allouhi, Amine
Abstract: The development of novel grid-connected integrated renewable energy systems for sustainable residential buildings is vital. The aim of this paper is to analyze the energy, economic and environmental performance of a novel grid-connected renewable energy system consisting of solar hybrid PV-Thermal collectors, wind turbine and sensible heat storage. The new integrated system serves concurrently hot water and electricity loads to a single-family building located in Laayoune, Morocco. The system adopts a stratified thermal storage and an auxiliary back-up to satisfy continuously the thermal load. Energy interaction between the examined system, load and grid is predicted at regular time intervals of 0.25 h. For a wind capacity of 1.2 kW, PV-T thermal collectors with a total area of 2.84 m 2 and a storage tank of 0.3 m 3, the system was able to satisfy 43.08% and 64.8% of the electric and heat demand, respectively. Compared to three other power supply scenarios, the economic assessment of the proposed configuration revealed that its Net Present Cost (NPC) is lower by 20.7%, 10.7% and 11.5% compared to grid only, PV-T only and wind only scenarios, respectively. As such, the novel system presents promising development perspectives especially that it allows additionally a reduction of up to 54% in the annual CO2 emissions compared to the conventional energy supply mode relying entirely on the electric grid. Highlights: A novel hybrid PV-T/Wind system with thermal storage for electricity and heat generation Self-consumption and self-sufficiency ratios are 90.25% and 43.08%, respectively. Net present Cost of the proposed system is significantly lower than other options The system can achieve an annual CO2 emission reduction of 54%